Issues in Recent Banking Crises in Developing Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper compares experiences with banking crises in seven countries in order to analyze the factors governing the crises and the effectiveness of measures to deal with the problems. The linkages between deregulation of the financial sector, and financial crises are examined. The portfolio shifts during crisis periods are studied. The major lesson from these experiences is that the regulatory and portfolio weaknesses in the financial sector have strong effects on the macroeconomy and can exacerbate the costs of macroeconomic adjustment. Structural measures to correct these weaknesses are important for the effectiveness of adjustment policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet